Is intraoperative corticosteroid a good choice for postoperative pain relief in total joint arthroplasty? A meta-analysis of 11 randomized controlled trials. Issue 40 (8th October 2021) - Zhang, Lu-kai; Zhu, Fang-bing; Gao, Huan-huan; Zhang, Lei; Quan, Ren-fu
Abstract: Background: Effective postoperative analgesia is of great significance for postoperative rehabilitation. This meta-analysis aimed to investigate the efficacy of corticosteroid on pain following total joint arthroplasty. Method: PubMed (1996–December 2020), Embase (1996–December 2020), and the Cochrane Library (CENTRAL, December 2020) were searched and a total of 11 randomized controlled trials met our inclusion criteria. Results: Eleven randomized controlled trials met the inclusion criteria. Pooled data indicated the corticosteroid group was effective compared to the control group in terms of the visual analogue scale at rest ( P  < .05) and movement ( P  < .05), the total morphine equivalent consumption ( P  < .05), and the length of stay ( P  < .05), without increasing the risk of periprosthetic joint infection ( P  = .74) and the length of stay ( P  = .32). Conclusions: Compared to the control group, intraoperative corticosteroid was benefit to the pain management in total joint arthroplasty.